Academic scholarship in light of the 2008 financial crisis: Textual analysis of NBER Working Papers - Daniel Levy; Tamir Mayer; Alon Raviv (Bar-Ilan University, Department of Economics, 2020)
Textual analysis of the NBER Working Papers published during 1999-2016 is done to assess the effects of the 2007-2009 crisis on the academic literature. The volume of crisis-related WPs is counter-cyclical, lagging the financial-instability-index. WPs by the Monetary-Economics, Asset-Pricing, and Corporate-Finance program members, hardly refer to "crisis/crises" in the pre-crisis period. As the crisis develops, however, their study-efforts of crisis-related issues increase rapidly, focusing on the links between 'Repo-and-Securitization' and the crisis. In contrast, WPs in macroeconomics-related programs refer extensively to "crisis/crises" in the pre-crisis period. These WPs abandon topics of 'Sudden-Stop' and 'Emerging-Markets' as the crisis developed.
Keywords: A11; C38; C55; E32; E44; E52; E58; F30; G01; G20; G21; G28; 330; 2008 Financial Crisis; Financial Crises; Textual Analysis; LDA Topic Modeling; Securitization; Repo; Sudden Stop